2011
DOI: 10.1161/hypertensionaha.111.179226
|View full text |Cite
|
Sign up to set email alerts
|

Low Birth Weight Infants Do Not Have Capillary Rarefaction at Birth

Abstract: Abstract-Low birth weight predicts adult essential hypertension and is linked to increased cardiovascular mortality in adult life. A reduction in capillary density (ie, rarefaction) is a hallmark of essential hypertension, and evidence suggests that rarefaction precedes the onset of the rise in blood pressure, because it is found in normotensive individuals at high risk of developing hypertension, suggesting that rarefaction is likely to be a primary structural abnormality. We hypothesized that low birth weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 45 publications
1
9
2
Order By: Relevance
“…We have previously reported that LBW infants born at term or preterm to mothers with normotension do not have CR: instead, these infants have a significantly higher CD at birth compared with their normal birth weight (NBW) counterparts. 10 Our findings appeared to contrast with reports that functional and structural microcirculatory abnormalities, including CR, are already present in childhood and young adulthood, respectively, in individuals born with LBW. 11–16 We, therefore, conducted a longitudinal study of a large cohort of infants from birth over a 1-year period.…”
contrasting
confidence: 99%
See 1 more Smart Citation
“…We have previously reported that LBW infants born at term or preterm to mothers with normotension do not have CR: instead, these infants have a significantly higher CD at birth compared with their normal birth weight (NBW) counterparts. 10 Our findings appeared to contrast with reports that functional and structural microcirculatory abnormalities, including CR, are already present in childhood and young adulthood, respectively, in individuals born with LBW. 11–16 We, therefore, conducted a longitudinal study of a large cohort of infants from birth over a 1-year period.…”
contrasting
confidence: 99%
“…Basal CD (BCD), which represents functional CD, was calculated as the mean of these 4 microscopic fields. We then used venous congestion to maximize the number of visualized perfused skin capillaries 10,17,18 by applying a size-appropriate neonatal blood pressure (BP) cuff around the calf muscle. The cuff was then inflated and maintained at 30 mm Hg for 2 minutes to determine the maximal CD (MCD), which represents the structural (anatomical) CD.…”
Section: Methodsmentioning
confidence: 99%
“…Whereas reduced capillary number has been identified as a specific vascular abnormality in young adults with a family predisposition, 30 individuals born with low birthweight do not consistently demonstrate changes in capillary density. 31 We also observed a lack of association between birthweight and capillary density in our preterm study. The finding of reduced capillary density relating to preterm birth per se is more established, even when blood pressure differences are still relatively modest.…”
Section: Discussionmentioning
confidence: 40%
“…[54][55][56][57] Surprisingly, low birth weight infants do not have capillary rarefaction at birth. 58 In low birth weight infants, capillary density may be even higher because of the relative systemic hypoxia that these infants experienced in utero. 56 Basal capillary density decreases progressively after the first week of life because of a process of pruning.…”
Section: Microcirculatory Dysfunction: Cause or Consequence Of Hypertmentioning
confidence: 99%
“…Alternatively, a "catch-up" process with abundant availability of nutrients may cause capillary hyperpruning. 59 Follow-up studies on the neonatal cohort described by D'Souza et al 58 have to be awaited to decide on this hypothesis.…”
Section: Microcirculatory Dysfunction: Cause or Consequence Of Hypertmentioning
confidence: 99%